The proteinpolysaccharides of human costal cartilage - Lawrence Rosenberg; Blanche Johnson; Maxwell Schubert (The Journal of Clinical Investigation, 1969)
Water-soluble proteinpolysaccharides, called PPL, can be extracted from bovine nucleus pulposus in yields of 45%, and from bovine nasal cartilage in yields of 37% of the dry tissue weight. From human costal cartilage only 7% can be extracted. The method used to separate PPL from each of the first two tissues into four distinct fractions separates the PPL of human costal cartilage into four fractions called PPL 3, PPL 4, PPL 5, and PPL 6, which show an increase in protein content, a decrease in chondroitin sulfate content, a nearly constant keratan sulfate content, and an increase in ease of sedimentability and molecular weight. From each of the three tissues mentioned. PPL 3 has a similar amino acid profile and so does PPL 5, but PPL 5 differs from PPL 3 in having a lower content of serine and higher contents of aspartic acid, tyrosine, and arginine. A more extensive effort to characterize these products has been made by analytical ultracentrifugation, and this has led to a further fractionation of PPL 5. Treatment of the cartilage residue or the water-insoluble protein polysaccharide called PPH, with neutral NH2OH solution releases water-soluble protein polysaccharides which in composition resemble PPL 4. The water-insoluble residue left after NH2OH treatment, when treated with collagenase, yields two soluble products, one resembling PPL 5 in composition, the other with a much lower chondroitin sulfate and much higher keratan sulfate content. The possibility is suggested that in human costal cartilage, binding of some forms of PPL to collagen may occur. Images